Practice and Barriers toward Breast Self-Examination among Palestinian Women in Gaza City, Palestine - Suha Baloushah; Waliu Jawula Salisu; Aymen Elsous; Maryam Muhammad Ibrahim; Fadia Jouda; Hanan Elmodallal; Zahra Behboodi Moghadam (The Scientific World Journal)
Breast self-examination (BSE) is one of many first-line screening practices aimed at early detection and prevention of fatal outcomes of breast cancer. The present study aimed to identify Palestinian women’s practices, awareness, and barriers to BSE. Using descriptive-analytical methods, a previously validated questionnaire was administered to a conveniently selected sample of women. The study was conducted among women who visited primary health clinics (PHCs) in Gaza City. A total of 390 participants who met the selection criteria answered the self-administered questionnaires. We used SPSS version 24.0 to analyze the data. The findings suggest that the practice of BSE among women in Gaza is low, with only 40% of the study participants reporting that they never practiced BSE before, even though 76.7% reported that they were aware of BSE. In general, the main barriers to BSE practices were that participants had wrong perceptions and lacked knowledge about BSE. Others also reported fear of detecting breast cancer as a barrier. The practice of BSE among Palestinian women in the Gaza Strip is low and marred with trivial issues as barriers that could be eliminated with dedicated and extensive educational campaigns in the area.